Innovation and Artificial Intelligence in Libraries and Information Centers - Zencir, Mithat Baver (Information World, 2024)
It has been aimed to review the book titled “Innovation and Artificial Intelligence in Libraries and Information Centers” in this study. The book examines the issues of innovation and artificial intelligence, including their reflections on libraries and information centers. The book can be considered an important resource for practitioners and researchers in the field of librarianship and information science who want to gain knowledge about relevant topics and examine application examples.